2014
DOI: 10.1002/mana.201300149
|View full text |Cite
|
Sign up to set email alerts
|

Critical point equation on four‐dimensional compact manifolds

Abstract: The aim of this article is to study the space of metrics with constant scalar curvature of volume 1 that satisfies the critical point equation frakturLg*(f)=Ric˚, for simplicity CPE metrics. It has been conjectured that every CPE metric must be Einstein. Here, we shall focus our attention for 4‐dimensional half conformally flat manifolds M4. In fact, we shall show that for a nontrivial f,M4 must be isometric to a sphere double-struckS4 and f is some height function on S4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 17 publications
0
36
0
3
Order By: Relevance
“…(In fact, this result can be improved for three dimensional manifolds. For more details, please see [21]; also see [1] for a four dimensional result).…”
Section: Introductionmentioning
confidence: 99%
“…(In fact, this result can be improved for three dimensional manifolds. For more details, please see [21]; also see [1] for a four dimensional result).…”
Section: Introductionmentioning
confidence: 99%
“…Barros and Ribeiro Jr [3] showed that Conjecture 1 is also true for 4-dimensional half conformally flat manifolds. We highlight that CP 2 endowed with Fubini-Study metric shows that the half-conformally flat condition is weaker than locally conformally flat condition in dimension 4.…”
Section: Conjecture 1 (1980's [4]) a Cpe Metric Is Always Einsteinmentioning
confidence: 98%
“…But, since |∇ f | 2 is constant in Σ c follows that H is constant on Σ, so is µ (see also [3]). Then, we may use Codazzi's equation to infer Similarly, we can use (3.8) jointly with (3.2) to conclude that C i j1 = 0 when {i, j} = {1, 2, 3, 4}.…”
Section: Proof Of Theorem 11mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Lafontaine proved that the CPE conjecture is true under conformally flat assumption with KerL * g (λ) = 0. Recently, Barros and Ribeiro Jr [3] proved that the CPE conjecture is also true for half conformally flat. Another partial proof of the CPE conjecture was presented by Yun, Chang and Hwang [12].…”
Section: Introductionmentioning
confidence: 98%